2022
DOI: 10.1111/jvim.16551
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography features of discospondylitis in dogs

Abstract: Background Computed tomography (CT) findings of dogs with discospondylitis have not been widely described despite increased availability of this imaging modality. Objectives Describe the CT features of discospondylitis in a population of clinically affected dogs with discospondylitis diagnosed by magnetic resonance imaging (MRI). Animals Forty‐one dogs (63 affected discs) with MRI‐identified discospondylitis presented to a single referral hospital between 2012 and 2022. Methods Retrospective, single center, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…While many studies have reported radiographic, CT, and MRI features of discospondylitis in dogs, data on comparative imaging findings is more limited 6,8,9,13,21 . In our study, a radiographic diagnosis of discospondylitis had a fair agreement with a CT diagnosis, but a reduced level of agreement with MRI.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…While many studies have reported radiographic, CT, and MRI features of discospondylitis in dogs, data on comparative imaging findings is more limited 6,8,9,13,21 . In our study, a radiographic diagnosis of discospondylitis had a fair agreement with a CT diagnosis, but a reduced level of agreement with MRI.…”
Section: Discussioncontrasting
confidence: 60%
“… 7 Characteristic CT features of discospondylitis included endplate erosion, osteolysis, and periosteal proliferation adjacent to the intervertebral disc spaces. 8 Characteristic MRI features of discospondylitis were STIR hyperintensity of the intervertebral discs and endplates, or endplates, contrast enhancement of the intervertebral discs, and increased T2 and decreased T1 signal intensity of soft tissues ventral to vertebral bodies. 4 , 9 , 10 All cases were diagnosed and managed by a board‐certified veterinary neurologist or an intern/resident under the guidance of a veterinary neurologist.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…18,19 Delayed diagnosis of discospondylitis can be detrimental to the prognosis, as both the vertebral lesion and neurological status can worsen with time. 18 Changes consistent with infection can be detected at earlier stages when using magnetic resonance imaging or computed tomography, compared with radiography [20][21][22] ; however, these imaging modalities can be cost prohibitive. Often the progression of disease at the time of presentation is substantial, warranting pain management.…”
Section: Discussionmentioning
confidence: 99%